Communication network architecture with 6G capabilities for urban air mobility - Al-Rubaye, Saba; Conrad, Christopher; Tsourdos, Antonios (Institute of Electrical and Electronics Engineers (IEEE), 2024)
As the demand for urban air mobility (UAM) increases, a robust communication, navigation, and surveillance (CNS) network architecture is needed to support the integration of sustainable UAM vehicles and technologies. Specifically, a new digital communication infrastructure is imperative to support increased levels of digitisation and autonomy within the aviation industry. This infrastructure must remain compatible with existing technologies, while enabling the integration of future 6G systems. This paper thereby discusses the communication challenges and opportunities associated with UAM integration. Potential communication technologies and standards needed to support UAM operations are presented and consolidated into a unified communication architecture with ground-, air-, and satellite-based infrastructure. The functional requirements of this architecture are also discussed, to enable seamless communication between UAM vehicles, air traffic control, and other ground- or air-based systems. Notably, 6G is highlighted as a key enabler of dense and sustainable UAM operations with high data traffic demands. A simple link budget analysis for a 6G air-to-ground data link in a green urban environment is thereby performed, em-phasising the infrastructural development necessary to support 6G roll-out. These findings pave the way for a more sustainable and accessible UAM transportation system, backed by a secure and reliable communication infrastructure.
Keywords: 6G; advanced air mobility; architecture; communication; urban air mobility